(untitled) (Milan Law Review, 2024)
The necessity to provide new guidance to States parties on ensuring equal and inclusive representation of women in decision-making systems according to Articles 7 and 8 of the CEDAW Convention presupposes a renewed vision of global and local governance that in my opinion passes through the reconsideration of the principle of the rule of law and its ability to avoid arbitrary power. On the one hand, a women-friendly rule of law should emphasize the demands of participation in deliberation and consultation in decision-making processes, both in formal and in informal settings. On the other hand, a women-friendly rule of law gets along with a horizontal reading of the rule of law able to detect violations in inequalities and discriminations often conveyed by bias and stereotypes. Among the requirements of the rule of law, explainability and accessibility to justice, but also to those essential goods – including access to technologies – necessary for an equal inclusion, could make the difference.